Molecular Characterization, Evolution, and Expression Profiling of the Dirigent (DIR) Family Genes in Chinese White Pear (Pyrus bretschneideri) - Cheng, Xi; Su, Xueqiang; Muhammad, Abdullah; Li, Manli; Zhang, Jinyun; Sun, Yanming; Li, Guohui; Jin, Qing; Cai, Yongping; Lin, Yi (Frontiers in Genetics, 2018)
Stone cells content and size are the key factors determining the internal quality of the pear fruit. Synthesis of lignin and thickening of secondary cell wall are the keys to the development of stone cells. The polymerization of monolignols and secondary cell wall formation requires the participation of dirigent proteins (DIRs). In recent years, DIR family have been studied in higher plants, but lack of comprehensive study in the pear DIR (PbDIR) family. This study focuses on the identification and analysis of PbDIR family for the first time. We identified 35 PbDIRs from the pear genome, 89% of which are intronless genes. Phylogenetic tree and chromosome localization analysis showed that 35 PbDIRs were divided into four subfamilies (DIR-a, -b/d, -e, and -g) and irregularly distributed among 10 chromosomes. In addition, we identified 29, 26 and 14 DIRs from the other three Rosids (peach, Mei and grape), respectively. Interspecies microsynteny analysis revealed the collinear gene pairs between pear and peach are the most. Temporal expression analysis showed that the expression changes of seven PbDIRs (DIR-a subfamily: PbDIR4 and PbDIR5; DIR-b/d subfamily: PbDIR11; DIR-g subfamily: PbDIR19; DIR-e subfamily: PbDIR23, 25 and 26) in fruits were consistent with the changes of fruit lignin and stone cells contents. In addition, the subfamily of PbDIRs in fruits showed significant responses after treatment with ABA, SA and MeJA. According to the protein tertiary structure, key amino acid residues and expression patterns analysis found that PbDIR4 might be involved in the metabolism of lignin and related to stone cells contents in pear fruits. In this study, we systematically analyzed the structure, evolution, function and expression of PbDIR family, which not only confirmed the characteristics of PbDIR family, but also laid the foundation for revealing the role of DIR in pear stone cell development and lignin polymerization.